1968
DOI: 10.1111/j.1365-2621.1968.tb01465.x
|View full text |Cite
|
Sign up to set email alerts
|

The phenolic compounds of blackcurrant juice and their protective effect on ascorbic acid

Abstract: Model systems of ascorbic acid in citrate buffer have been used to investigate the antioxidant effect of flavonols, phenolic acids, anthocyanins and extracts of blackcurrant juice for ascorbic acid. In the presence and absence of added copper salts the flavonol aglycones, and quercetin in particular, gave positive protection to the ascorbic acid, but the anthocyanins showed no antioxidant properties except in the presence of copper. The stability of ascorbic acid in blackcurrant juice has been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Antioxidant capacity of natural apple juice is mainly attributed to phenol antioxidants (87%) and ascorbic acid (6%) [23], while Tikekar et al [24] described a decrease in ascorbic acid content during UV irradiation, up to 0.7–1.0 mg/min at 0.03 J/cm 2 . However, no significant changes ( p > 0.05) in ascorbic acid content after UV treatment were observed, due to the protective effect of phenols [25] and pigments [18,19]. Diminution in TEAC by UV treatment effect was probably due to non-phenol antioxidant oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant capacity of natural apple juice is mainly attributed to phenol antioxidants (87%) and ascorbic acid (6%) [23], while Tikekar et al [24] described a decrease in ascorbic acid content during UV irradiation, up to 0.7–1.0 mg/min at 0.03 J/cm 2 . However, no significant changes ( p > 0.05) in ascorbic acid content after UV treatment were observed, due to the protective effect of phenols [25] and pigments [18,19]. Diminution in TEAC by UV treatment effect was probably due to non-phenol antioxidant oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In real foods the presence of metal ions like copper and iron, and light would accelerate the reaction (Allwood, ). Clegg and Morton () reported that quercetin had the highest protection of vitamin C in a citric buffer (with and without Cu 2+ ) compared to kaempferol, chlorogenic acid, p ‐coumaric acid, and anthocyanin‐glycosides because of an ortho ‐hydroxylation of the quercetin structure. Although old, this seems to be the only paper dealing with this issue.…”
Section: Resultsmentioning
confidence: 99%
“…However, little attention has been given to its preservation in foods, especially when it is naturally present. Possible stabilizers for vitamin C include cysteine hydrochloride (Mohamed, Kyi, & Sharif, ), protamine (Yamauchi, Nimura, & Kinoshita, ), and phenolic compounds found in blackcurrant juice (Clegg & Morton, ; Harper, Morton, & Rolfe, ).…”
Section: Introductionmentioning
confidence: 99%